REFERENCE GROUPS, FAMILY, ROLES AND STATUS ON YOUNG CONSUMER BAHVIOR TOWARDS PURCHASE INTENTIONS OF LUXURY FASHION BRANDS - Kembau, Agung; Mekel, Peggy Adeline (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Today, luxury consumption has become so popular, everyone aspire for luxury, particularly in fashion. Recently young consumers consumption`s pattern is not only to satisfy basic physiological needs but also to create a self and define one’s role in society. One of the most interesting aspects of consumption is luxury consumption which is not vital for young consumer’s survival but they are engaging in the consumption of luxury products. This research aims to analyze (1) what is the influence of social factors (reference group, family, roles and status) on young consumer behavior towards purchase intention of luxury fashion brand; (2) to identify which factors of social factors that has the most significant influence on young consumer behavior towards purchase intention of luxury fashion brand. The research method that used in this research associative with multiple linear regression analysis technique, as sample of the research 100 respondent taken from people in Manado as young consumers. The findings revealed that reference groups, family, and roles & status have a significant effect to the young consumer purchase intention on luxury fashion brands. Young people with their uniqueness wants to get the attention of the people around them, they wants other people to like the luxury fashion goods they buy. Company or shop should improve the prestige of their product increase their product image. Keywords: reference group, family, roles and status, purchase intention